Composite coatings of Co-W(WО₂)-TiO₂ to production of electrolytic hydrogen - Yermolenko, Iryna Yuriyivna; Sakhnenko, Mykola Dmytrovych; Karakurkchi, Hanna Volodymyrivna; Saray, Vasyl' Volodymyrovych; Halytsya, Vitaliy Ivanovych; Zyubanova, Svitlana Ivanivna (Cognum Publishing House, 2022)
The influence of electrolysis regimes and deposition conditions on the composition and morphology of composite coatings Co-W(WOx)-TiO2 was studied. It is shown that the application of a current density of 1.5-2.5 A/dm2, a temperature of 45 ‒ 50 °C and slow mixing of the working solution (up to 100 rpm) creates the conditions for the incorporation of titanium dioxide into the metal matrix of the coating, and tungsten in the form of oxides of variable valence. The use of an ultrasonic disperser allows increasing the tungsten content in the coating to 10 at. %; the content of the dispersed phase is preserved. Using scanning electron and atomic force microscopy, the influence of the nature and content of tungsten and titanium dioxide on the morphology and topography of the coatings was established.
Keywords: electrolytic hydrogen; electrolysis; composite coatings; titanium oxides; tungsten